2018
DOI: 10.1111/jgs.15457
|View full text |Cite
|
Sign up to set email alerts
|

Frequent 911 Fall Calls in Older Adults: Opportunity for Injury Prevention Strategies

Abstract: Certain older individuals are at risk of having multiple fall-related calls to EMS over short periods of time, sometimes within hours of previous calls. In our current healthcare system, no significant intervention or follow-up is offered or available by emergency first response teams to prevent subsequent falls. This study demonstrates the need for a paradigm change in our healthcare system that helps reduce resource utilization for the first responder community for fall-related calls in older adults and re-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Deployment of EMS for lift assists diverts care from high acuity emergencies and can cost a single community millions of dollars in lost revenue 24 . High 9‐1‐1 utilizers are common with 43% of repeat callers calling ≥3 times and 1% calling EMS ≥10 times after an initial fall call 24 . Alarmingly, over 60% of older adults who use EMS for a lift assist die or have additional emergency visits within 6 months 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Deployment of EMS for lift assists diverts care from high acuity emergencies and can cost a single community millions of dollars in lost revenue 24 . High 9‐1‐1 utilizers are common with 43% of repeat callers calling ≥3 times and 1% calling EMS ≥10 times after an initial fall call 24 . Alarmingly, over 60% of older adults who use EMS for a lift assist die or have additional emergency visits within 6 months 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, EMS providers who are called to older adults’ homes to provide lift assists are in a prime position to assess further fall risk and provide education and brief interventions to prevent these older adults from falling again [23]. The ED is also a logical place for multifactorial fall risk assessment and brief interventions for older adults with fall injuries.…”
Section: Discussionmentioning
confidence: 99%
“…They therefore aim to reconfigure their role to enable them to engage in (and be reimbursed for) chronic disease management, preventive care, and postdischarge follow-up visits. 27,28,[36][37][38][39] Forging partnerships with senior housing providers fits well with an EMS approach emphasizing community health.…”
Section: What This Study Addsmentioning
confidence: 98%
“…It can also result from preventable health issues: poorly managed medications, 24 for example, or unsafe living environments. 25,26 EMS providers also frequently respond to calls that do not result in ED transfers: the prime example is "lift assists," when EMS providers are called to help older adults get up after falling; calls of this type can indicate broader, intensifying health care needs [27][28][29][30] and represent a significant amount of EMS business; one study found that 21% of falls-related EMS trips for older adults did not result in an ED transfer; 28 one small study found the 5% of all EMS calls were lift-assists. 27 Because such calls are uncompensated by insurance, EMS providers are motivated to support efforts to reduce their frequency.…”
Section: Introductionmentioning
confidence: 99%